Deep-subwavelength broadband sound absorbing metasurface based on the update finger coiling-up method. (30th June 2022) - Wu, Yutao; Liang, Qingxuan; He, Jin; Feng, Jiaming; Chen, Tianning
Highlights: An update finger coiling-up method that can be used to design deep-subwavelength broadband sound absorbing metasurfaces is proposed. The finger coiling-up method can improve the sound absorption coefficient and working bandwidth of the unit without increasing the thickness. Compared with classic coiling-up method, the proposed method can simplify the complexity of the metasurface structures to facilitate fabrication. Abstract: The bulky structure of traditional sound-absorbing materials limits its application to control low-frequency noise, and new deep-subwavelength low-frequency broadband acoustic materials have an urgent need. This paper proposes an update finger coiling-up method, which can improve the sound absorption coefficient and working bandwidth of the unit without increasing the thickness. In addition, the complexity of the structure can be simplified to facilitate manufacturing. The influence of the typical parameters of the unit on the sound absorption performance and the coupling performance of the unit are also studied. Finally, by combining 16 finger coiled-up units, a metasurface with continuous broadband sound absorption in the range of 375 Hz to 855 Hz is obtained, and the average sound absorption coefficient is above 0.85. In particular, the thickness of the metasurface is only 38 mm, which is 1/24 of the corresponding operating wavelength at 375 Hz. The proposed update finger coiling-up method provides a new idea for reducing the thickness of sound-absorbing materials, which will have good application prospects in noise control field.